2018
DOI: 10.1038/s41397-018-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

A non-functional galanin receptor-2 in a multiple sclerosis patient

Abstract: Multiple Sclerosis (MS) is an inflammatory neurodegenerative disease that affects approximately 2.5 million people globally. Even though the etiology of MS remains unknown, it is accepted that it involves a combination of genetic alterations and environmental factors. Here, after performing whole exome sequencing, we found a MS patient harboring a rare and homozygous single nucleotide variant (SNV; rs61745847) of the G-protein coupled receptor (GPCR) galanin-receptor 2 (GALR2) that alters an important amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The genes harboring rare disease-causing variants for familial MS, herein or previously described [912], play critical roles in cellular cation homeostasis, and the regulation of transcription and activation of inflammatory mediators; suggesting a disruption of the innate immune system as the common underlying biological mechanism for the initiation of MS symptoms (Fig 3). Variants in PLAU , MASP1 , and C2 , as well as risk alleles in PLG and PLAU [6, 20], suggests a disruption in the fibrinolysis and complement cascade in response to microbial threads or cellular debris as a trigger for MS.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The genes harboring rare disease-causing variants for familial MS, herein or previously described [912], play critical roles in cellular cation homeostasis, and the regulation of transcription and activation of inflammatory mediators; suggesting a disruption of the innate immune system as the common underlying biological mechanism for the initiation of MS symptoms (Fig 3). Variants in PLAU , MASP1 , and C2 , as well as risk alleles in PLG and PLAU [6, 20], suggests a disruption in the fibrinolysis and complement cascade in response to microbial threads or cellular debris as a trigger for MS.…”
Section: Discussionmentioning
confidence: 90%
“…In these families, rare variants co-segregating with MS are likely to account for the highest attributable risk towards the disease; however, additional genetic and environmental factors are expected to play a significant role in the presentation of clinical symptoms, level of disability, disease progression, penetrance and onset age [8, 9]. The application of whole-exome sequencing (WES) in MS families has already nominated pathogenic mutations in NR1H3 , P2RX4/P2RX7 , NLRP1 and GALR2 [912]. Although only one of these discoveries has been replicated [13], mutations responsible for Mendelian forms of MS highlight the molecular mechanisms underlying the cause of disease, and provide the means for the generation of new cellular and animal models of MS based on human genetic etiology [9].…”
Section: Introductionmentioning
confidence: 99%
“…GAL 2 R has, for instance, been reported to be neuroprotective in experimental autoimmune encephalomyelitis and a cuprizone model mimicking aspects of multiple sclerosis [70,71]. A non-functional GAL 2 R in a multiple sclerosis patient has been reported [72], indicating a potential therapeutic role for stimulation of GAL 2 R in this disease. The current study raises the possibility of an antiobesity effect of M89b that could be confirmed via chronic or repeated administration in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the IMSGC case-control exome chip study analyzing the role of rare coding variants suggests that a further ∼10% of MS heritability may be explained by rare (Minor Allele Frequency < 0.05) variants (4). Neither these substantial gene discovery efforts nor smaller pedigree designs have discovered any reproducible single-gene causes of MS (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Although rare monogenic forms of MS not captured in these studies cannot be excluded, these data argue for MS being a prototypical complex and polygenic disease.…”
Section: The Genetic Contribution To Ms Risk Key Pointsmentioning
confidence: 89%